1973
DOI: 10.1177/00220345730520021001
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental Caries Experience Related to Age, Sex, Race, and Certain Salivary Properties

Abstract: Saliva flow, protein concentration, and blood group substance concentration in the whole saliva of 106 persons were compared. Some of these variables then were compared with age, decayed surfaces, DMF surfaces, and immunoglobulin concentration (IgA and IgG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These results would imply that the IgA/ml is decreasing with age in this young sample. Everhart et al [1973] found that age and IgA/ml were not significantly correlated in their total sample. Thus young children may secrete higher concentrations of IgA than the adult population.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These results would imply that the IgA/ml is decreasing with age in this young sample. Everhart et al [1973] found that age and IgA/ml were not significantly correlated in their total sample. Thus young children may secrete higher concentrations of IgA than the adult population.…”
Section: Discussionmentioning
confidence: 78%
“…Lehner et al [1967], Everhart et al [1972Everhart et al [ , 1973 and recently Orstavik and Brandtzaeg [1975] presented data that sub stantiates this possibility. In their studies, significant negative correlations of salivary IgA and caries were found in the teenage and young adult population.…”
mentioning
confidence: 87%
“…The mean salivary IgG levels in the present study were higher in Group I as compared to Group II; however, the difference was statistically insignificant. Lehner et al [10] and Everhart et al [24] reported that salivary IgG does not seem to play any role in prevention of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming majority of our subjects were Caucasians but the subjects in their study were mostly Hispanic. Several studies have observed not only differences in caries prevalence among people with diverse racial/ethnic backgrounds, but also variation in salivary protein composition (Everhart et al, 1973;Johnson, 2005;Zakhary et al, 2007;Sivakumar et al, 2009). However, no racial/ ethnic differences in AMP expression or genetic polymorphisms have yet been confirmed.…”
Section: Discussionmentioning
confidence: 99%